Relationship Between Knowledge And Attitude Of Adolescent Women About Reproductive Health With Premenstruation Syndrome In Lingkungan V Kelurahan Ladang Bambu Kecamatan Medan Tuntungan Of The Year 2021 - Suriati Lubis; Sari Rahma Fitri (Institute of Computer Science (IOCS), 2022)
Premenstrual syndrome is a combination of changes in psychological and physical symptoms that occurs in the luteum phase of menstruation and begins almost immediately before menstruation. The research method is analytic observational with a cross sectional approach. The population of this study were all 174 adolescent women. Sampling by means of random samples as many as 37 people. The results of the statistical test used were the chi-squer statistical test =0.05. The results of the analysis showed that from 37 respondents there were 13 people (35.1%) who had good knowledge and 13 people who had sufficient knowledge the majority did not experience premenstrual syndrome by 8 people (61.5%) and 17 people who had a negative attitude and who experienced premenstrual syndrome. 17 people (100%), the results of the chi-square statistic obtained a knowledge value of p = 0.04 and an attitude value of p = 0.00 < = 0.05 which means that there is a relationship between knowledge and attitudes of adolescent women about reproductive health with premenstrual syndrome. It is hoped that adolescent women will actively seek information about reproductive health so that adolescent women know how to prevent and treat premenstrual syndrome